2008
DOI: 10.1021/cm802393z
|View full text |Cite
|
Sign up to set email alerts
|

P-Redox Mechanism at the Origin of the High Lithium Storage in NiP2-Based Batteries

Abstract: The Li reactivity of NiP2 is investigated by means of electrochemical tests, in situ XRD, and 31P NMR characterizations as well as first principles DFT calculations. A two-step insertion/conversion reaction is shown to transform the NiP2 starting electrode into an intermediate Li2NiP2 single phase and then to convert into the Li3P/Ni° nanocomposite. The ternary phase is fully characterized and is shown to be structurally very close to the starting NiP2 regarding the Ni ions environment. This demonstrates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 27 publications
4
85
0
Order By: Relevance
“…Density function theory (DFT) calculations have revealed that the very covalent nature of the M-P bonds yields electronic structures around the Fermi level (i.e., the electronic states involved in the redox activity of the compounds) in which bands with a strong P(3 s ,3 p ) character lie at high energy. [232][233][234][235] As a matter of fact, the attractive redox activity of phosphorus has led to efforts to investigate the performance of a Li-P battery. [ 236 ] While no conversion has been observed for phosphides containing early transition metals such as Ti or V, [237][238][239] …”
Section: Nickelmentioning
confidence: 99%
See 1 more Smart Citation
“…Density function theory (DFT) calculations have revealed that the very covalent nature of the M-P bonds yields electronic structures around the Fermi level (i.e., the electronic states involved in the redox activity of the compounds) in which bands with a strong P(3 s ,3 p ) character lie at high energy. [232][233][234][235] As a matter of fact, the attractive redox activity of phosphorus has led to efforts to investigate the performance of a Li-P battery. [ 236 ] While no conversion has been observed for phosphides containing early transition metals such as Ti or V, [237][238][239] …”
Section: Nickelmentioning
confidence: 99%
“…Both the cubic and the monoclinic polymorphs convert to Li 3 P and Ni, with a intermediate step of insertion for the latter, [ 235 ] upon discharge to 0 V, producing a total of 1000-1300 mAh g − 1 . [ 234 ] Fair reversibility is observed upon the fi rst charge, and the capacity in powder electrodes decays noticeably within the fi rst 10 cycles, even at low rates.…”
Section: Ironmentioning
confidence: 99%
“…FeP n with n = 0.33, 0.5, 1, 2, and 4 have been intensively investigated by Monconduit and coworkers (Boyanov et al 2006(Boyanov et al , 2009a. A closed and condensed polyhedral structure of FeP 6 octahedra is present in FeP, opening up some channels between the corner-shared polyhedra in FeP 2 , and finally leading to a layered structure of edgesharing octahedra in the case of FeP 4 .…”
Section: D Transition Metal Active Materialsmentioning
confidence: 99%
“…NiP 2 prepared via a solid-state route from the elements (Boyanov et al 2009a) and by ball milling (Hayashi et al 2009) has been tested in a common battery setup using liquid electrolytes and by a solid electrolyte, respectively. A two-step intercalation/conversion mechanism has been identified during the lithiation/delithiation process via a solid solution Li 1.5 NiP 2 -Li 2 NiP 2 to Li 3 P and Ni.…”
Section: D Transition Metal Active Materialsmentioning
confidence: 99%
“…Density Functional Theory (DFT) calculations have revealed that the high covalent nature of the M-P yields electronic structures around the Fermi level in which levels with a strong P(3s, 3p) character lie at high energy. 27 In the present work, electrodeposited Co 2 P films are prepared under a galvanostatic regime. The high potential reaction with lithium of theses phases as opposed to potential reaction found in other metal phosphides as CoP 3 and CoP is highlighted.…”
mentioning
confidence: 99%